Multiorgan impairment in low-risk individuals with post-COVID-19 syndrome: a prospective, community-based study. Issue 3 (30th March 2021) - Dennis, Andrea; Wamil, Malgorzata; Alberts, Johann; Oben, Jude; Cuthbertson, Daniel J; Wootton, Dan; Crooks, Michael; Gabbay, Mark; Brady, Michael; Hishmeh, Lyth; Attree, Emily; Heightman, Melissa; et al.
Abstract : Objective: To assess medium-term organ impairment in symptomatic individuals following recovery from acute SARS-CoV-2 infection. Design: Baseline findings from a prospective, observational cohort study. Setting: Community-based individuals from two UK centres between 1 April and 14 September 2020. Participants: Individuals ≥18 years with persistent symptoms following recovery from acute SARS-CoV-2 infection and age-matched healthy controls. Intervention: Assessment of symptoms by standardised questionnaires (EQ-5D-5L, Dyspnoea-12) and organ-specific metrics by biochemical assessment and quantitative MRI. Main outcome measures: Severe post-COVID-19 syndrome defined as ongoing respiratory symptoms and/or moderate functional impairment in activities of daily living; single-organ and multiorgan impairment (heart, lungs, kidneys, liver, pancreas, spleen) by consensus definitions at baseline investigation. Results: 201 individuals (mean age 45, range 21–71 years, 71% female, 88% white, 32% healthcare workers) completed the baseline assessment (median of 141 days following SARS-CoV-2 infection, IQR 110–162). The study population was at low risk of COVID-19 mortality (obesity 20%, hypertension 7%, type 2 diabetes 2%, heart disease 5%), with only 19% hospitalised with COVID-19. 42% of individuals had 10 or more symptoms and 60% had severe post-COVID-19 syndrome. Fatigue (98%), muscle aches (87%), breathlessness (88%) and headaches (83%) were most frequently reported. Mild organ impairment was present in the heart (26%), lungs (11%), kidneys (4%), liver (28%), pancreas (40%) and spleen (4%), with single-organ and multiorgan impairment in 70% and 29%, respectively. Hospitalisation was associated with older age (p=0.001), non-white ethnicity (p=0.016), increased liver volume (p<0.0001), pancreatic inflammation (p<0.01), and fat accumulation in the liver (p<0.05) and pancreas (p<0.01). Severe post-COVID-19 syndrome was associated with radiological evidence of cardiac damage (myocarditis) (p<0.05). Conclusions: In individuals at low risk of COVID-19 mortality with ongoing symptoms, 70% have impairment in one or more organs 4 months after initial COVID-19 symptoms, with implications for healthcare and public health, which have assumed low risk in young people with no comorbidities. Trial registration number: NCT04369807; Pre-results .